Establishment of the first Chinese national standard for protein subunit SARS-CoV-2 vaccine. Issue 14 (25th March 2022) - Gao, Fan; An, Chaoqiang; Bian, Lianlian; Wang, Yiping; Zhang, Jialu; Cui, Bopei; He, Qian; Yuan, Yadi; Song, Lifang; Yang, Jinghuan; Yan, Xujia; Xu, Kangwei; et al.
Abstract: A reference standard is needed for quality control of protein subunit SARS-CoV-2 vaccines to meet urgent domestic needs. The Chinese National Institutes for Food and Drug Control (NIFDC) launched a project to establish the first reference material for the protein subunit SARS-CoV-2 vaccine to be used for calibration of antigen testing. The potency and stability of the national candidate standard (CS) were determined by collaborative calibration, and accelerated and freeze–thaw degradation studies. Moreover, a suitability study of the CS was performed. Eight laboratories in mainland China were asked to detect antigen content of CS using a common validated enzyme-linked immunosorbent assay (ELISA) kit established by NIFDC and in-house kits in the collaborative study. Six laboratories returned valid results, which established that the antigen content of the CS was 876, 938 YU/mL, with good agreement across laboratories. In the suitability study, the CS exhibited excellent parallelism and a linear relationship with four samples produced by different expression systems and target proteins. In addition, good stability in the accelerated and freeze–thaw degradation study was observed. In conclusion, the CS was approved by the Biological Product Reference Standards Sub-Committee of the National Drug Reference Standards Committee as the first Chinese national standard for determining antigen content of protein subunit SARS-CoV-2 vaccines, with an assigned antigen content of 877, 000 U/mL (Lot. 300050–202101). This standard will contribute to a standardized assessment of protein subunit SARS-CoV-2 vaccine in China and may provide experience for developing reference materials for antigen content detection of SARS-CoV-2 vaccine in other countries.